Organizational Climate and Job Performance of Workers from the Huancavelica Province Municipality - De La Cruz Quispe, Naida Gladys (2023)
The purpose of this research paper is to determine whether organizational climate positively and significantly influenced the job performance of workers from the Huancavelica Province Municipality in 2019, in order to improve their quality of life and provide high-quality service to users from Huancavelica. This research is descriptive, quantitative, correlational, and non-experimental. The results obtained after applying the questionnaires meet validity and reliability standards. Analytic, synthetic, inductive, and deductive techniques were used. The research population consisted of 192 individuals; 53 individuals were selected through non-probability sampling, and classified according to similar occupations. Pearson’s r was used to validate the results of the statistical analysis, resulting in positive and significant correlation with job performance. The coefficient of determination (r) between both variables is 81.93% and the significance level (p) is over 0.05. Therefore, the work environment in which employees grow and develop is a crucial factor to determine their performance, both positively and negatively.